Advanced water treatment process by simultaneous coupling granular activated carbon (GAC) and powdered carbon with ultrafiltration: Role of GAC particle shape and powdered carbon type. (1st March 2023) - Zhang, Jingyu; Yu, Sijia; Wang, Jingwei; Zhao, Zhi-Ping; Cai, Weiwei
Highlights: Compared with PAC-UF, severer fouling occurred with biochar-UF without GAC. PAC uniformly dispersed on membranes, while biochar tended to agglomerate. RGAC exhibited optimal fouling reduction performance with lowest energy consumption. Substantial amounts of small-sized PC were released by two cylindrical-shaped GACs. RGAC-biochar-UF achieved commensurate effluent quality but better permeability. Abstract: In current ultrafiltration systems, limited removal for small-sized contaminants and membrane fouling remain longstanding obstacles to overcome. Herein, a novel process by simultaneous coupling powered carbon (PC) and fluidized granular activated carbon (GAC) with ultrafiltration was proposed aiming to achieve high effluent quality and mitigated membrane fouling. This study conducted mechanistic explorations on the performances of different-shaped GAC particles on fouling control and PC release during fluidization, meanwhile comparing the utilizations of powdered activated carbon (PAC) and biochar in terms of their adsorption, deposition and interactions with aquatic contaminants during filtration. The results showed that the effluent COD of biochar-UF was slightly higher than PAC-UF attributed to lower specific surface area and pore volume present on biochar. Compared with PAC-UF, the biochar-UF without fluidized GAC exhibited higher fouling propensity due to more organics attached on membranes via bridging with Ca 2+ released by the biochar. Concurrently, distinct morphologies were found for PAC and biochar depositions, where PAC uniformly dispersed on membranes but biochar tended to agglomerate. Interestingly, fluidized spherical GAC (RGAC) with highest particle momentum and least energy consumption appeared highly effective in reducing fouling associated with biochar, and the overall fouling rate of RGAC-biochar-UF was even lower than RGAC-PAC-UF system. More importantly, substantial amount of small-sized PC was released by two cylindrical-shaped GACs, which were determined to be around 12–16 mg/L in contrast to merely 3.4 mg/L produced from RGAC. Consequently, the RGAC-biochar-UF system achieved commensurate effluent quality but better permeability than RGAC-PAC-UF along with a 20% expenditure saved, which might be a promising water treatment system more suitable for large-scale applications. Graphical abstract: Image, graphical abstract